Introducing Porphyrin Units by Random Copolymerization Into NDI-Based Acceptor for All Polymer Solar Cells - Liu, Jinliang; Li, Mengzhen; Chen, Dong; Huang, Bin; He, Qiannan; Ding, Shanshan; Xie, Wenquan; Wu, Feiyan; Chen, Lie; Chen, Yiwang (Frontiers in Chemistry, 2020)
Naphthalene diimide (NDI)-based polymer N2200 is a promising organic polymer acceptor for all-polymer solar cells (all-PSCs), but its inherent shortcomings like poor extinction coefficient and strong aggregation limit further performance optimization of all-PSCs. Here, a series of random copolymers, PNDI-Px were designed and synthesized by introducing porphyrin unit into NDI-based polymer as acceptors for all-PSCs. These random copolymers show higher absorption coefficient, raised the lowest unoccupied molecular orbital (LUMO) energy levels than N2200. The crystallinity can also be fine-tuned by regulation of the content of porphyrin unit. The random copolymers are matched with polymer donor PBDB-T for the application in all-polymer solar cells. The best power conversion efficiency (PCE) of these PNDI-Px-based devices is 5.93%, ascribing to the all-over enhanced device parameters compared with N2200-based device. These results indicate that introducing porphyrin unit into polymer is a useful way to fine-tune the photoelectric performance for efficient all-PSCs.